Clinical evaluation of a novel multipoint radiofrequency ablation device to treat chronic rhinitis. Issue 2 (16th March 2023) - Reh, Douglas D.; Lay, Kristopher; Davis, Greg; Dubin, Marc G.; Yen, David M.; O'Malley, Ellen M.; Sillers, Michael
Abstract: Objective: Safety and efficacy of the NEUROMARK® system for treating chronic rhinitis. Methods: A prospective, single‐arm, multicenter study was performed on adults with chronic rhinitis who underwent radiofrequency ablation to the posterior nasal nerves. Primary endpoints were device‐related serious adverse events (SAEs) at 1 month and change from baseline in visual analog scale nasal symptom scale (VAS NSS) for rhinorrhea and nasal congestion at 3 months. Total nasal symptom score (rTNSS) and mini Rhinoconjunctivitis Quality of Life Questionnaire (mini RQLQ) score were also evaluated. Results: Thirty‐six participants were enrolled and completed follow‐up at 1 and 3 months. Mean VAS NSS scores for rhinorrhea and nasal congestion demonstrated significant improvement at 3 months (both p < .0001). The mean percent changes from baseline in VAS rhinorrhea and nasal congestion were 53% and 55%, respectively. Total scores and all individual rTNSS items significantly improved (all p < .001) over the measured interval. Percent responder rate (≥30% reduction from baseline in total rTNSS) at 3 months was 78%. The total mean mini RQLQ scores, as well as all subdomains, improved significantly (all p < .0001). At 3 months, 89% of participants reported a minimal clinically important difference of ≥0.4 point improvement in the mini RQLQ score. No SAEs occurred during the study. Conclusions: The NEUROMARK System is a novel radiofrequency ablation device that provides safe and effective treatment to the posterior nasal nerves for patients with chronic rhinitis. Study participants experienced statistically significant and clinically meaningful improvement in symptoms and quality of life assessments at 3 months post‐procedure. Trial Registration: The study is registered at www.clinicaltrials.gov with the unique identifier of NCT05324397. Level of Evidence: 4. Abstract : The NEUROMARK System is a novel RF ablation device that provides safe and effective treatment to the posterior nasal nerves for patients with chronic rhinitis. Study participants experienced statistically significant and clinically meaningful improvements in symptoms and quality of life assessments at 3 months post‐procedure.